Adult sepsis – A nationwide study of trends and outcomes in a population of 23 million people. Issue 5 (November 2017) - Lee, Chien-Chang; Yo, Chia-Hung; Lee, Meng-tse Gabriel; Tsai, Kuang-Chau; Lee, Shih-Hao; Chen, Yueh-Sheng; Lee, Wan-Chien; Hsu, Tzu-Chun; Lee, Sie-Hue; Chang, Shy-Shin
Summary: Objectives: To determine the trend of incidence and outcome of sepsis based on a nationwide administrative database. Methods: We analyzed the incidence and mortality of both emergency department treated and hospital treated sepsis from 2002 through 2012 using the entire health insurance claims data of Taiwan. The national health insurance covers 99% of residents in Taiwan. Sepsis patients were identified using a set of validated ICD-9CM codes conforming to the sepsis-3 definition. The 30-day all-cause mortality was verified by linked death certificate database. Results: During the 11-year study period, a total of 1, 259, 578 episodes of sepsis was identified. The mean incidence rate was 639 per 100, 000 person-years, increasing from 637.8/100, 000 persons in 2002 to 772.1/100, 000 persons in 2012 (annual increase: 1.9%). The mortality rate, however, has decreased from 27.8% in 2002 to 22.8% in 2012 (annual decrease: 0.45%). The trend of incidence and mortality did not change after standardization by age and gender using 2002 as the reference standard. Conclusion: We showed that the incidence of sepsis has increased while the mortality has decreased in Taiwan. Despite the decreasing trend in sepsis mortality, the total number of sepsis mortality remains increasing due to the rapid increase in sepsis incidence. Highlights: Past sepsis epidemiology studies did not give an accurate estimate on the population incidence or mortality for sepsis. A novel methodology linking nationwide claims data to death certificate was used to determine the sepsis incidence and mortality. The incidence of sepsis increased from 637.8/100, 000 person-years in 2002 to 772.1/100, 000 in 2012 (20.9% increase). The mortality rate of sepsis has decreased from 27.8% in 2002 to 22.8% in 2012 (18.1% decrease). Although mortality showed a decreasing trend, the total number of patients dying of sepsis is still on the rise.